IMPLEMENTASI DISCOVERY LEARNING DENGAN PEMBUATAN ECOPRINT PADA MATA PELAJARAN IPAS UNTUK PENINGKATAN KREATIVITAS SISWA KELAS V SD NEGERI 4 KUBU BANGLI - Anak Agung Istri Diah Cika Swari; Ni Made Anggreni; Ni Kadek Supadmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to describe the implementation of the Discovery Learning model in Ecoprint-making activities, identify the challenges encountered by students, and analyze its impact on improving the creativity of fifth-grade students at SD Negeri 4 Kubu Bangli. The study employed a qualitative descriptive research design. The research subjects consisted of 23 fifth-grade students of SD Negeri 4 Kubu Bangli. Data were collected through observation, interviews, documentation, and literature review, and were analyzed using data reduction, data presentation, and conclusion drawing techniques. The findings revealed that the implementation of the Discovery Learning model in Ecoprint-making activities was carried out through six stages: stimulation, problem statement, data collection, data processing, verification, and generalization. The learning process actively engaged students in observing, experimenting, discussing, and drawing conclusions based on direct experiences. The challenges faced by students included limited prior knowledge of Ecoprint techniques, differences in creativity and skill levels, limited availability of materials, lack of self-confidence, and time constraints during practical activities. These challenges were addressed through intensive guidance, the provision of alternative materials, step-by-step demonstrations, and collaborative learning among students. The implementation of Discovery Learning through Ecoprint-making activities had a positive impact on students’ creativity, as reflected in their improved ability to generate ideas, flexibility in creating works, originality of products, active participation, enthusiasm, and confidence in expressing their ideas and presenting their work.